2004
DOI: 10.2460/javma.2004.224.1936
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of catheter-associated urinary tract infection among dogs in a small animal intensive care unit

Abstract: Results suggest that placement of an indwelling urinary catheter in dogs is associated with a low risk of catheter-associated UTI during the first 3 days after catheter placement, provided that adequate precautions are taken for aseptic catheter placement and maintenance. Results of bacterial culture of urinary catheter tips should not be used to predict whether dogs developed catheter-associated UTI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
0
4

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(103 citation statements)
references
References 10 publications
5
94
0
4
Order By: Relevance
“…A principal vantagem desse método é a sua realização sem a administração de substâncias exógenas e não haver a necessidade do emprego de equipamentos específicos. Entretanto, toda a urina produzida deve ser colhida, e falhas no procedimento de colheita podem resultar em resultados duvidosos (SMARICK et al, 2004).…”
Section: Taxa De Filtração Glomerular (Tfg)unclassified
“…A principal vantagem desse método é a sua realização sem a administração de substâncias exógenas e não haver a necessidade do emprego de equipamentos específicos. Entretanto, toda a urina produzida deve ser colhida, e falhas no procedimento de colheita podem resultar em resultados duvidosos (SMARICK et al, 2004).…”
Section: Taxa De Filtração Glomerular (Tfg)unclassified
“…Many researchers in veterinary nosocomial infections also included laboratory diagnosis for confirmation (Biertuempfel et al, 1981;Mathews et al, 1996;Lobetti et al, 2002;Smarick et al, 2004;Marsh-Ng et al, 2007;Bubenik and Hosgood, 2008;Jones et al, 2009) and some researchers have not included laboratory confirmation (Nicholson, 2002;Eugster et al, 2004;Ahern et al, 2010). Committing laboratory confirmation is not cost effective and also more time consuming which prevents immediate action during outbreaks.…”
Section: Laboratory Based Surveillancementioning
confidence: 99%
“…A prospective study conducted by Smarick and others in 2004 reported 10.3% of healthy catheterized dogs of both sex developed urinary tract infection. Furthermore this study revealed that female dogs are more susceptible to develop the urinary tract infection (Smarick et al, 2004). A randomized clinical trial was performed with dogs underwent intervertebral disk correction surgery.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
“…The ability to form biofilm is crucial for catheter-related infections [1] [2]. Differently from the human isolate CFT073, all the 21 animals isolates were different in the ability to form biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…The urinary tract infection is a common location for bacterial infection in both humans and dogs [1] [2]. Many virulence factors are associated with the ability of the uropathogenic Escherichia coli (UPEC) to cause disease in humans [3]- [5].…”
Section: Introductionmentioning
confidence: 99%